2004
DOI: 10.1002/ps.962
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of allyl acetate as a fumigant against five stored grain beetle pests

Abstract: Five esters, butyl acetate, allyl acetate, ethyl acetoacetate, isopropyl acetate and propyl acetate, were screened as fumigants in the laboratory for 24 h at 27 (+/-2) degrees C against the adults of Rhyzopertha dominica (F), Sitophilus oryzae (L) and Tribolium castaneum (Herbst). Of the compounds tested, allyl acetate was the most toxic, with LD(99) values of 7.56, 12.81 and 11.42 mg litre(-1) against R dominica, S oryzae and T castaneum, respectively. Tests with allyl acetate against mixed-age cultures of Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Numbers of dead insects were determined at 3, 6, 12 and 24 h after exposure. (Rajendran and Muralidharan 2005;Leelaja et al 2007). The number of insects knocked down at the time points (3 -24 h) and percentage mortality were determined.…”
Section: Comparison Of Insect Toxicity With Chemical Fumigantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numbers of dead insects were determined at 3, 6, 12 and 24 h after exposure. (Rajendran and Muralidharan 2005;Leelaja et al 2007). The number of insects knocked down at the time points (3 -24 h) and percentage mortality were determined.…”
Section: Comparison Of Insect Toxicity With Chemical Fumigantsmentioning
confidence: 99%
“…Cloth bags containing mixed-age cultures of individual species were placed individually in 850 ml screw cap glass bottles that served as the fumigation chambers. The impregnated filter paper was then attached to the under surface of the screw cap of a glass bottle (850 ml) (Rajendran and Muralidharan 2005).…”
Section: Grain Treatmentmentioning
confidence: 99%
“…The extracts and essential oils have demonstrated antimicrobial and insecticidal activity (Deans and Svoboda 1989;Regnault-Roger et al 2004;Pavela 2006;Mahmoodi et al 2014). The plant's essential oils have various insecticidal activity such as contact toxicity (Asawalam et al 2006;Ogendo et al 2008), repellence (Kéita et al 2001;Rozman et al 2007), fumigant toxicity (Lee et al 2003;Rajendran and Muralidharan 2005;Shojaaddini et al 2008), and antifeedant effects (Saxena et al 1992). Several studies have reported insecticidal effects of A. annua extract containing growth retardation, antifeedant, and larvicidal effects (Haghighian et al 2008;Shekari et al 2008;Hasheminia et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The stored product insects lesser grain borer ( Rhyzopertha dominica) and rice weevil ( Sitophilus oryzae L.) were reared on whole wheat, and the rust-red flour beetle ( Tribolium castaneum Herbst.) on wheat flour with 5% yeast; the pulse beetle ( Callosobruchus chinensis ) was reared on whole green gram as described elsewhere 43 . Housefly ( Musca domestica) larvae were reared in a mixture of sterilized bran, milk powder and water, and the adults were allowed free access to water and thick paste of condensed milk and milk powder 44 .…”
Section: Methodsmentioning
confidence: 99%